If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36 + -1y = -36 Solving 36 + -1y = -36 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + -1y = -36 + -36 Combine like terms: 36 + -36 = 0 0 + -1y = -36 + -36 -1y = -36 + -36 Combine like terms: -36 + -36 = -72 -1y = -72 Divide each side by '-1'. y = 72 Simplifying y = 72
| 7a+3n+3a= | | 4d+12=42 | | x+2+7=40 | | 42-(3c+4)=2(c+4)+c | | 2x+3(2x+15)=125 | | 10(-11-4p)-2p=2(-1-3p) | | 8x-5=1+6x | | 2+675n+80=2310 | | 2+675+80n=2310 | | -8y+5(y+2)=-11 | | 2x+6-7=5-4x | | 4x(x-3)=15 | | 67+5/2x=92 | | 4x+4.2x=5 | | X+3+7=40 | | -46=-6t-8 | | -2+9=16x-5-15x | | 2n+675+80=2310 | | 4x+4.2=5 | | p+8-2=10 | | 5(s-4)-s=4s-20 | | x-8.2=-5.2 | | 4(4)+8y=40 | | 3=6-8n-3 | | 8-c=30 | | 7-10(1-10a)=11a+8(9a-11) | | 2x-5(3)=17 | | s+37=14 | | r+2s-(-3r)-s= | | 7x+(4x-14)=105 | | k+10-2=5 | | 675n+80=2310 |